DYNAMICS OF ROOT AND TUBER CROPS ACREAGE ALLOCATION AND YIELD ADJUSTMENT IN NIGERIA - Sadiq, M. S.; Karunakaran, N.; Singh, I. P. (International Journal of Research -GRANTHAALAYAH, 2019)
This paper empirically studied the growth pattern and supply response of root and tuber crops farmers in Nigeria using annual time series data sourced from FAO database. The data spanned from 1961-2014 and covered area, yield and price of yam, cassava and potatoes crops. The data were analyzed using the growth model, instability index, production decomposition analysis model and Engel-Granger two-step model. Findings showed that area was responsible for the paradigm shift in the production of selected root and tuber crops in Nigeria and not productivity which is very essential for sustainable agriculture due to shrinking of land resource owing to competing demand for its use as evidenced by incessant attacks of herdsmen on arable crop farmers. Generally, the farmers respond to price incentives in reallocating their area and adjusting their yield for all the selected crops. It was also observed that acreage and yield for all the selected crops had long-run association with the price and non-price factors; likewise, it established long-run equilibrium. So the need for price forecast mechanism to checkmate cob-web cycle which affects the balance between supply and demand for the root and tuber crops in the country and increase in production of crops achieved by increasing productivity of land-combination of technology and efficiency in the utilization of resources is recommended.